Design of UWB Antenna with WLAN & X-Band Notch for Wireless Communication - V.Prashanth, K; Tejasri, A; Sandeep, K; Sateesh Kumar, U; Swarupa, G (International Journal of Engineering and Technology, 2018)
In this proposition, a traditional UWB antenna with twofold indent channels was intended for a few remote applications. The exhibited antenna is outlined having estimations of 30 Ã— 35 Ã— 1.6 mm3 with a fix of rectangular staircase design. The dismissal bands are WLAN at 5 GHz (5.1 - 5.8 GHz) and the satellite X-band from space to earth (7.25 - 7.75 GHz). The patch with a step design with a modified Ï€-formed opening gets the ultra-wide band. The UWB scope of 3.1 - 10.6 GHz affirmed by FCC can possibly cause interferences in the various wireless systems applications.. With a specific end goal to lessen these interferences, we settled on the band indent. In this proposed outline, the WLAN has scores setting a U-molded opening in the patch and the X-band has indents with a reversed T-shape in the ground plane.Â Â Â